Platelet increment is not associated with endothelial damage in haematological patients: a prospective observational study. (18th August 2019) - Benediktsson, S.; Kander, T.; Ostrowski, S. R.; Johansson, P. I.; Thomas, O. D.; Schött, U.
Abstract: The aim of this study was to investigate if thrombocytopenic haematology patients show signs of endothelial damage when transfused with platelets and if that damage correlates with platelet increment measured with corrected count increment (CCI). Endothelial damage secondary to radiation or chemotherapy may lead to consumption of transfused platelets but research in this field is scarce. Patients were divided into four groups: Group 1: Acute leukaemia; Group 2: Autologous stem cell transplantation (SCT); Group 3: Allogenic SCT; and Group 4: patients receiving platelets prior to interventions. Blood was sampled before (baseline) and immediately after (0 h) transfusion and then at 1, 4, 8, 16 and 24 h after transfusion. The biomarkers syndecan-1, soluble thrombomodulin (sTM) and vascular endothelial growth factor (VEGF) were analysed. The plasma concentration differences between baseline and later sampling times were referred to as delta (Δ). Fifty-four platelet transfusion events were studied. All biomarkers were within the normal ranges both before and after the transfusions. The Δsyndecan-1 increased at 0 h ( p  = .02), but there was no significant correlation between Δsyndecan-1 and CCI. There was no change in any of the other biomarkers after transfusion compared to before. There were no differences between the groups and no correlations were found between CCI and C-reactive protein, Δsyndecan-1, ΔsTM or ΔVEGF. There were no signs of endothelial damage before or after platelet transfusions. A transient significant change in syndecan-1 immediately after platelet transfusion did not influence platelet count or platelet CCI. Trial registration: ClinicalTrials.gov identifier: NCT02601131.